Konsepsi jihad dalam konteks kehidupanmodern: pemikiran Sayyid Sabiq dan Abu Bakar Jabir al-Jazayri - Idri Shaffat (State Institute of Islamic Studies (IAIN) Salatiga, 2011)
Recently, the term of jihad has been used by certain people for improper purposes. At the time of theProphet and the classical Islamic period, jihad meant as an effort to uphold and fight for Islam with awealth, soul, body, mind, and deeds. Nowdays certain people have been understanding and applyingthis term in the form of terror. They understand it solely as ‘the holy war’ against the unbelievers withparadise as a reward for martyrs who died for it. In the name of jihad, in this decade there are manybombings in Indonesia and other hemisphere. Bomb terrors not only occur in non-Muslim countriesbut also in Muslim countries which also cause Muslim victims. The question then is what are theiractions really the jihad as it is thought by Islam? To answer this question, this paper tries to explain theconcept of jihad in the perspective of two scholars who live in contemporary era, namely Sayyid Sabiqand Abu Bakr Jabir al-Jazayri by examining definition of jihad concept, legal basis and implementationof jihad, categories of jihad, and orientation of jihad understanding in the context of modern life.Through this study it is expected that the solution of jihad formulation in the context of modern lifecan be clarified and resolved.